Preserving Heritage: The Maintenance of National Heritage Anglican Churches in Malaysia - Shirley Jin Lin Chua; Azlan Shah Ali; Wee Fhong Ow (Penerbit UTHM, 2025)
This book is a journey through time and space, through ornate arches and intricately carved pews, and through the hearts of those who have tirelessly ensured the conservation of these Anglican churches. It is a testament to the unwavering faith that binds communities and transcends the boundaries of time and culture. As the custodians of this cultural and spiritual legacy, it is with great pride and reverence that we present this book. It serves as an exploration of the intricate fusion of faith and heritage, offering a window into the soul of Malaysia. Through these pages, we invite you to embark on a journey of discovery, understanding, and appreciation for the monumental task of preserving our national heritage. We are deeply grateful to the Malaysian Department of National Heritage, architects, custodians, conservators, historians, volunteers, and all those who have generously shared their knowledge and experiences to make this project possible. Without their dedication, this book would remain an unfulfilled dream. May the pages that follow inspire an enduring commitment to the maintenance and preservation of our National Heritage Anglican Churches, ensuring that they stand as timeless symbols of faith, culture, and history for generations to come.